The Effect of Environmental Performance, Eco-Efficiency, and Cash Holding on Firm Value - Zen, Syfa; Sofie (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2023)
This study aims to determine whether there is a relationship between the three variables, namely, environmental performance, eco-efficiency, and cash holding on firm value. To analyze the data, the researchers used multiple linear regression with the purposive sampling technique. The data were obtained from the Annual Report and Financial Report of manufacturing companies on subsector consumer non-cyclical listed on the Indonesia Stock Exchange from 2019 to 2021. The results of the study show that the environmental performance, eco-efficiency, and cash holding variables have a significant positive effect on firm value.